Hedge fund analysis : an in-depth guide to evaluating return potential and assessing risks - Travers, Frank J. (Wiley, 2012)
"Hedge Fund Analysis will provide a broad framework covering the hedge fund due diligence process from initial screening to analytical techniques, interviewing skills, and legal and contract negotiations. Having guided the reader through the selection process, it will demonstrate a variety of mechanisms for monitoring and tracking hedge funds and the underlying hedge fund portfolios. This comprehensive guide will explain each stage of the process in minute detail, providing specific examples which fully explain the benefits and pitfalls that can occur on each step of the way. Every analytic tool and technique available will be explored, and arguments will be supported with examples of real situations. This book has five sections. Section 1 will provide a detailed background and illustration on how to source hedge funds and how to screen through them (there are 7,000+ of them out there, so screening is critical). Section 2 will lay out a thorough process for evaluating the funds, from initial interviewing to performance analysis to a primer of interviewing techniques, including both verbal and non verbal communication (body language). Section 3 will break out what questions to ask by strategy. It is important to know what key risk factors are by strategy and to ask the "right" questions. Each major strategy will have its own chapter that will discuss the strategy, associated risks and a detailed list of questions (along with right and wrong responses). Section 4 incorporates non-investment analysis such as operational due diligence and risk management. Section 5 shows how to evaluate all the components of the due diligence process to rank a hedge fund's strengths and weaknesses. This section will also cover how to put together a portfolio of hedge funds and how to monitor investments once they are made"--